Highly elastic, strong, and reprocessable cross-linked polyolefin elastomers enabled by boronic ester bonds. Issue 19 (20th April 2020) - Yang, Fei; Pan, Li; Ma, Zhe; Lou, Yahui; Li, Yuanyuan; Li, Yuesheng
Abstract : Despite the development of new catalysts and synthetic strategies to prepare polyolefin elastomers (POEs), less progress has been made in balancing their elastomeric properties with processability and resistance to heat and solvents. Abstract : Despite the development of new catalysts and synthetic strategies to prepare polyolefin elastomers (POEs), less progress has been made in balancing their elastomeric properties with processability and resistance to heat and solvents. The long-standing challenge is that the customary introduction of a permanent cross-linking network often sacrifices the reprocessability and the elongation at break for the heat and solvent resistances. In this work, we utilized boronic ester bonds to introduce robust but reversible crosslinks in POEs, which endowed materials with excellent mechanical properties and resistance to heat and solvents without sacrificing their reprocessability and elasticity. These novel POE vitrimers were prepared from anthracene-containing ethylene/α-olefin copolymers that were grafted with the dioxaborolane maleimide (DM) complementary exchange group and cross-linked with bis-dioxaborolane (DB). The POE vitrimer with a DB/DM ratio of 0.2 exhibits a tensile strength of up to 15 MPa, the elongation at break of up to 1200%, and the elastic recovery of up to 90% at 1000% strain. The persistent crosslinks allow POE vitrimers to exhibit excellent resistance to heat and various organic solvents. In the meantime, we further demonstrated that the POE vitrimers relax quickly at elevated temperatures and can be recycled without significant loss of elastomeric properties. All results show that the integration of reversible boronic ester bonds through a D–A reaction is a promising strategy to improve the overall performance and reliability of POE materials.